2022
DOI: 10.3390/en15082891
|View full text |Cite
|
Sign up to set email alerts
|

Net Hydrogen Consumption Minimization of Fuel Cell Hybrid Trains Using a Time-Based Co-Optimization Model

Abstract: With increasing concerns on transportation decarbonization, fuel cell hybrid trains (FCHTs) attract many attentions due to their zero carbon emissions during operation. Since fuel cells alone cannot recover the regenerative braking energy (RBE), energy storage devices (ESDs) are commonly deployed for the recovery of RBE and provide extra traction power to improve the energy efficiency. This paper aims to minimize the net hydrogen consumption (NHC) by co-optimizing both train speed trajectory and onboard energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Zhang et al [19] introduced the Mixed Integer Linear Programming (MILP) model to optimize the speed profile and the capacity configuration for on-board HESDs, which focused on minimum economic costs considering the long-term train operation. In [20], the authors showed that the capacity of SCs and speed trajectory for Fuel-cell hybrid trains could be co-optimized to achieve minimum net hydrogen consumption. The distance-based model was proposed to obtain the speed trajectory and capacity solution with energy flow constraints [21].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [19] introduced the Mixed Integer Linear Programming (MILP) model to optimize the speed profile and the capacity configuration for on-board HESDs, which focused on minimum economic costs considering the long-term train operation. In [20], the authors showed that the capacity of SCs and speed trajectory for Fuel-cell hybrid trains could be co-optimized to achieve minimum net hydrogen consumption. The distance-based model was proposed to obtain the speed trajectory and capacity solution with energy flow constraints [21].…”
Section: Introductionmentioning
confidence: 99%
“…All the highlighted advantages make hydrogen potentially a better choice than batteries in energy-demanding applications. For example, they could be implemented in heavy-duty vehicles to satisfy the energy demand in the transportation sector which accounts for almost a quarter of the total energy demand of the globe [26]. Studies have shown that fuel cell-powered heavy-duty vehicles offer better range, vehicle longevity, and significantly lower transportation and maintenance costs [27].…”
Section: Introductionmentioning
confidence: 99%